2018
DOI: 10.1016/j.anbehav.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Collective exodigestion favours blow fly colonization and development on fresh carcasses

Abstract: 26Necrophagous flies breeding on carcasses face high selection pressures and therefore 27 provide interesting opportunities to study social adaptations. We postulated that blowfly 28 necrophagous larvae gregariousness is an adaptive response to the environmental 29 constraints of fresh carcasses. Cooperation is indeed believed to be a key to the global 30 success of social species. To test this idea, the development of Lucilia sericata 31 (Diptera: Calliphoridae) larvae growing on low-or high-digestibility foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 83 publications
(2 reference statements)
0
49
0
Order By: Relevance
“…Clustering was shown to speed up the process of media liquefaction in vials (Dombrovski et al 2017 ) that could in turn facilitate and speed up food ingestion. A more complex explanation features a phenomenon of communal exodigestion that is mostly observed among various fly larvae feeding on flesh and other high-protein substrates (Scanvion et al 2018 ) but was also documented in Drosophila (Gregg et al 1990 ). Larvae are able to secrete a variety of enzymes that digest external polymers (amylose, cellulose and even chitin), therefore reducing energy expenditure per individual animal required to process and ingest a food source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clustering was shown to speed up the process of media liquefaction in vials (Dombrovski et al 2017 ) that could in turn facilitate and speed up food ingestion. A more complex explanation features a phenomenon of communal exodigestion that is mostly observed among various fly larvae feeding on flesh and other high-protein substrates (Scanvion et al 2018 ) but was also documented in Drosophila (Gregg et al 1990 ). Larvae are able to secrete a variety of enzymes that digest external polymers (amylose, cellulose and even chitin), therefore reducing energy expenditure per individual animal required to process and ingest a food source.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, highly efficient foraging aggregations that enhance survival rates compared to solitary foragers are documented in sawfly larvae (Ghent 1960), various species of caterpillars (Clark and Faeth 1997), where animals reared in larger groups displayed higher developmental rates and increased survival. This is also true for corpse-devouring necrophagous flies (Scanvion et al 2018;Aubernon et al 2019). Importantly, factors that provide trophic benefits can serve as tradeoffs in case of severe overcrowding (e.g., overly elevated temperature and proteotoxic stress caused by excessive tissue digestion, exemplified by Rivers et al 2011), implying a complex nonlinear pattern of relationship between group size (Cash et al 1993) and composition (Trowbridge 1991), food availability and distribution (Monaghan and Metcalfe 1985), presence or absence of predators (Turchin and Kareiva 1989) and individuals' investment into cooperative efforts (Valone 1989;Courchamp 1999;Giraldeau and Caraco 2018;Lindstedt et al 2018).…”
mentioning
confidence: 99%
“…Neither adult body size, nor female fertility were measured in these experiments. First, because previous development studies in our laboratory showed that the body size of flies did not differ significantly (Scanvion et al ., ), and, second, because the determination of the fertility of each fly would have raise several technical problems and exceeded the time frame of the present study.…”
Section: Methodsmentioning
confidence: 88%
“…In previous experiments (Scanvion et al ., ), differences in development rates and final sizes between individuals are reported. This plasticity exists not only between different developmental conditions, but also under constant biotic and abiotic parameters (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation